Depth wavenumber spectral decomposition based on orthogonal matching pursuit and its application in hydrocarbon reservoir prediction - Tian TANG; Suyu BA; Ruikun SHI; Nan WANG; Yuan TIAN; Hanming GU (地质科技通报, 2024)
Objective Conventional seismic attribute analysis in the time domain is based on the conversion from prestack depth migration data to time domain data, which will cause the loss of effective high-frequency information. To make full use of the advantage of the high imaging accuracy of depth domain data, it is necessary to carry out the attribute analysis of depth domain data. Because the wavenumber in the depthdomain is related to the frequency and wave velocity, obtaining a high-resolution depth wavenumber spectrum is the key to seismic attribute analysis in the depth domain. Methods In this paper, based on the spectral decomposition method of sparse inversion, an overcomplete wavelet dictionary in the depth domain is established, and the orthogonal matching pursuit algorithm is used to improve the computational resolution of the depth wavenumber spectrum. By calculating the attributes of the depth wavenumber spectrum of the theoretical model and comparing them with the attributes of the time-frequency spectrum, the variation characteristics of the depth wavenumber spectrum of the hydrocarbon reservoir are analyzed. Through the application of depth wavenumber spectral attribute analysis of field data, the practicability of using the depth wavenumber spectrum to predict oil and gas reservoirs is verified. Results The results show that the depth wavenumber spectral decomposition method based on the orthogonal matching pursuit algorithm has high resolution and can be used as a high-precision method for hydrocarbon reservoir prediction in the depth domain. Conclusion The application of field data shows that the low-wavenumber shadow appears below the oil and gas reservoir in the deep wavenumber spectrum, which can be used as a sign to indicate the existence of oil and gas reservoirs in the depth domain. The depth wavenumber spectral decomposition based on orthogonal matching pursuit can effectively identify the low-wavenumber shadow anomaly, which enables to predict the oil and gas reservoirs by use of the depth domain seismic data.